Genomic Comparison and Spatial Distribution of Different Synechococcus Phylotypes in the Black Sea - Di Cesare, Andrea; Dzhembekova, Nina; Cabello-Yeves, Pedro J.; Eckert, Ester M.; Slabakova, Violeta; Slabakova, Nataliya; Peneva, Elisaveta; Bertoni, Roberto; Corno, Gianluca; Salcher, Michaela M.; Kamburska, Lyudmila; Bertoni, Filippo; et al. (Frontiers in Microbiology, 2020)
Picocyanobacteria of the genus Synechococcus are major contributors to global primary production and nutrient cycles due to their oxygenic photoautotrophy, their abundance, and the extensive distribution made possible by their wide-ranging biochemical capabilities. The recent recovery and isolation of strains from the deep euxinic waters of the Black Sea encouraged us to expand our analysis of their adaptability also beyond the photic zone of aquatic environments. To this end, we quantified the total abundance and distribution of Synechococcus along the whole vertical profile of the Black Sea by flow cytometry, and analyzed the data obtained in light of key environmental factors. Furthermore, we designed phylotype-specific primers using the genomes of two new epipelagic coastal strains - first described here - and of two previously described mesopelagic strains, analyzed their presence/abundance by qPCR, and tested this parameter also in metagenomes from two stations at different depths. Together, whole genome sequencing, metagenomics and qPCR techniques provide us with a higher resolution of Synechococcus dynamics in the Black Sea. Both phylotypes analyzed are abundant and successful in epipelagic coastal waters; but while the newly described epipelagic strains are specifically adapted to this environment, the strains previously isolated in mesopelagic waters are able, in low numbers, to withstand the aphotic and oxygen depleted conditions of deep layers. This heterogeneity allows different Synechococcus phylotypes to occupy different niches and underscores the importance of a more detailed characterization of the abundance, distribution, and dynamics of individual populations of these picocyanobacteria.